Nietzsche's voices - Sallis, John, 1938- (Sallis, John, 1938- Works., 2022)
"Nietzsche's Voices , the latest volume of John Sallis's Collected Writings, presents his two-semester lecture course on Nietzsche offered in the Philosophy Department of Duquesne University during the school year 1971-72. "Nietzsche is easy to read; his is apparently the easiest of all the great philosophies. Yet the easy intelligibility is deceptive. Nietzsche's writings make us believe we have understood when in fact we have not. His philosophy is actually the exact opposite of easy," says Sallis. He first discusses Nietzsche's life and the relevance of the classical Greeks to his thought. Then, in invigorating detail, Sallis discusses Nietzsche's views on truth, morality, and the death of God. The final lecture covers Thus Spoke Zarathustra, Nietzsche's influential but highly debated work of philosophical fiction. Nietzsche's Voices represents an essential introduction to the thought of Friedrich Nietzsche, as presented by one of today's most significant philosophers"--